Surgery in disorders of sex development (DSD) with a gender issue: If (why), when, and how?. Issue 3 (June 2016) - Mouriquand, Pierre D.E.; Gorduza, Daniela Brindusa; Gay, Claire-Lise; Meyer-Bahlburg, Heino F.L.; Baker, Linda; Baskin, Laurence S.; Bouvattier, Claire; Braga, Luis H.; Caldamone, Anthony C.; Duranteau, Lise; El Ghoneimi, Alaa; Hensle, Terry W.; et al.
Summary: Ten years after the consensus meeting on disorders of sex development (DSD), genital surgery continues to raise questions and criticisms concerning its indications, its technical aspects, timing and evaluation. This standpoint details each distinct situation and its possible management in 5 main groups of DSD patients with atypical genitalia: the 46, XX DSD group (congenital adrenal hyperplasia); the heterogeneous 46, XY DSD group (gonadal dysgenesis, disorders of steroidogenesis, target tissues impairments …); gonosomic mosaicisms (45, X/46, XY patients); ovo-testicular DSD; and "non-hormonal/non chromosomal" DSD. Questions are summarized for each DSD group with the support of literature and the feed-back of several world experts. Given the complexity and heterogeneity of presentation there is no consensus regarding the indications, the timing, the procedure nor the evaluation of outcome of DSD surgery. There are, however, some issues on which most experts would agree: 1) The need for identifying centres of expertise with a multidisciplinary approach; 2) A conservative management of the gonads in complete androgen insensitivity syndrome at least until puberty although some studies expressed concerns about the heightened tumour risk in this group; 3) To avoid vaginal dilatation in children after surgical reconstruction; 4) To keep asymptomatic mullerian remnants during childhood; 5) To remove confirmed streak gonads when Y material is present; 6) It is likely that 46, XY cloacal exstrophy, aphallia and severe micropenis would do best raised as male although this is based on limited outcome data. There is general acknowledgement among experts that timing, the choice of the individual and irreversibility of surgical procedures are sources of concerns. There is, however, little evidence provided regarding the impact of non-treated DSD during childhood for the individual development, the parents, society and the risk of stigmatization. The low level of evidence should lead to design collaborative prospective studies involving all parties and using consensual protocols of evaluation.